Damping effects in Penning trap mass spectrometry - George, Sebastian; Blaum, Klaus; Block, M.; Breitenfeldt, M.; Dworschak, M.; Herfurth, F.; Herlert, A.; Kowalska, Magdalena A.; Kretzschmar, M.; Ramirez, E. Minaya; Neidherr, D.; Schwarz, S.; et al. (International journal of mass spectrometry, 2011)
Collisions of ions with residual gas atoms in a Penning trap can have a strong influence on the trajectories of the ions, depending on the atom species and the gas pressure. We report on investigations of damping effects in time-of-flight ion-cyclotron resonance mass spectrometry with the Penning trap mass spectrometers ISOLTRAP at ISOLDE/CERN (Geneva, Switzerland) and SHIPTRAP at GSI (Darmstadt, Germany). The work focuses on the interconversion of the magnetron and cyclotron motional modes, in particular the modification of the resonance profiles for quadrupolar excitation due to the damping effect of the residual gas. Extensive experiments have been performed with standard and Ramsey excitation schemes. The results are in good agreement with predictions obtained by analytical continuation of the formulae for the undamped case.